2022
DOI: 10.1088/1757-899x/1221/1/012059
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the Optical, Structural and electrochemical properties of PVC/PMMA/NiO blend films

Abstract: PVC/PMMA and PVC/PMMA/NiO blend films were prepared by solution casting technique. The FT-IR spectra confirms the change in the band structure and presence of hydrogen chlorine and Ni-O bond in the PVC/PMMA and NiO loaded blend film and XRD pattern reveals the formation of NiO phase in the PVC/PMMA polymer with exhibits the amorphous nature, it may increase the conductivity and stability of the material.The surface morphology shows the NiO homogeneously dispersed on the surface of PVC/PMMA matrix, and CV curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Ishaq et al 20 concluded that the mechanical and thermal characteristics of the PVC/PMMA were enhanced through filling with 5% iron oxide NPs. Also, Basappa et al 21 examined the electrochemical, optical, and structural characteristics of PVC/PMMA/NiO films. Results confirmed clear signs of good miscibility between the PVC/PMMA and NiO‐loaded PVC/PMMA blend films.…”
Section: Introductionmentioning
confidence: 99%
“…Ishaq et al 20 concluded that the mechanical and thermal characteristics of the PVC/PMMA were enhanced through filling with 5% iron oxide NPs. Also, Basappa et al 21 examined the electrochemical, optical, and structural characteristics of PVC/PMMA/NiO films. Results confirmed clear signs of good miscibility between the PVC/PMMA and NiO‐loaded PVC/PMMA blend films.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown, the absorption increases with the loading of PbO NPs within the blend matrix. In addition, there is an absorption band for most films located at 275 nm, which is attributed to electronic transitions with π–π* transitions 18 . It was observed that loading PbO NPs did not shift the band position.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, there is an absorption band for most films located at 275 nm, which is attributed to electronic transitions with π-π* transitions. 18 It was observed that loading PbO NPs did not shift the band position. Finally, this band could be coming from the unsaturated bonds (such as C O) in the studied films.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations